Endogenous ribosomal protein L29 (RPL29): a newly identified regulator of angiogenesis in mice - Jones, Dylan T. (The Company of Biologists Limited, 2013)
Cellular ribosomal protein L29 (RPL29) is known to be important in protein synthesis, but its function during angiogenesis has never been described before. We have shown previously that mice lacking β3-integrins support enhanced tumour angiogenesis and, therefore, deletion of endothelial αvβ3 can provide a method for discovery of novel regulators of tumour angiogenesis. Here, we describe significant upregulation of RPL29 in β3-null endothelial cells at both the mRNA and protein level. Ex vivo, we show that VEGF-stimulated microvessel sprouting was reduced significantly in Rpl29-heterozygous and Rpl29-null aortic ring assays compared with wild-type controls. Moreover, we provide in vivo evidence that RPL29 can regulate tumour angiogenesis. Tumour blood vessel density in subcutaneously grown Lewis lung carcinomas was reduced significantly in Rpl29-mutant mice. Additionally, depletion of Rpl29 using RNA interference inhibited VEGF-induced aortic ring sprouting, suggesting that anti-RPL29 strategies might have anti-angiogenic potential. Overall, our results identify that loss or depletion of RPL29 can reduce angiogenesis in vivo and ex vivo.